Is Invagination Anastomosis More Effective in Reducing Clinically Relevant Pancreatic Fistula for Soft Pancreas After Pancreaticoduodenectomy Under Novel Fistula Criteria: A Systematic Review and Meta-Analysis - Cao, Zhe; Luo, Wenhao; Qiu, Jiangdong; Liu, Yueze; Zheng, Lianfang; Zhang, Taiping (Frontiers in Oncology, 2020)
Objective: To define the effectiveness of different anastomosis on clinical relevant postoperative fistula in patients with soft pancreas using the newest version of the fistula definition and criteria. Background: Different criteria of clinical relevant Postoperative pancreatic fistula (POPF) make the optimal anastomosis technique remain controversial. Methods: PubMed, Embase, Web of Science, the Cochrane Central Library, and ClinicalTrials.gov were systematically searched up to 20 April 2020, and were evaluated by Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines. Randomized controlled trials comparing duct-to-mucosa anastomosis versus invagination anastomosis in pancreatic surgery were included. Result: Seven studies involving 1110 participants were included. Using the postoperative pancreatic fistula definition provided by the International Study Group of Pancreatic Surgery 2016, the incidence rate of grade B/C pancreatic fistula was significantly lower in patients experiencing invagination anastomosis than in those undergoing duct-to-mucosa anastomosis. Four of seven trials comparing invagination with duct-to-mucosa anastomosis in patients with a soft pancreas showed that invagination was significantly better than duct-to-mucosa anastomosis in controlling pancreatic fistula formation, but no significant difference was detected between the two anastomosis techniques in patients with a hard pancreas. No significant difference was explored between the two methods in the length of hospital stay or postoperative mortality rate. Conclusion: This study demonstrated superiority of invagination anastomosis over duct-to-mucosa anastomosis in reducing the risk of Grade B/C postoperative pancreatic fistula using the ISGPS 2016 definition, but it does not significantly reduce the mortality rate or length of hospital stay. The effect of invagination in reducing pancreatic fistula formation is obvious in patients with a soft pancreas, but there is no significant difference between the two anastomosis techniques in patients with a hard pancreas. We found a lower rate of clinically relevant postoperative pancreatic fistula in the invagination group in patients with a soft pancreas.